High performance multilevel converter topology for interfacing energy storage systems with medium voltage grids - Rashed, Mohamed; Klumpner, Christian; Asher, Greg (2010)
This paper proposes a high performance hybrid cascaded H-Bridge (HB) Multilevel Converter (MLC) with integrated Series Active Power Filter SAPF for interfacing energy storage systems with medium voltage grids. Isolated DC sources comprised of modular dual DC/DC converters and Medium Frequency Transformers MFT are used to energise the MLC HBs. The primary sides of the DC/DC converters are connected to a common low voltage DC bus, which is supplied by supercapacitors energy stacks. Simple hybrid stair-case/SVM modulation strategy is used to synthesise the converter output voltage waveforms and to guarantee even sharing of power between the converter’s HBs. The converter power losses and efficiency are evaluated and compared for two design cases of using small or large DC link capacitor banks. The converter is investigated under various operating conditions and the results show excellent dynamic and steady state performance.